Stock Performance Before And After Right Issue In Indonesia - Bambang Sutrisno (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
Right issue is the subsequent stock offerings that give priority to the existing shareholders to buy new shares at a specified price and time. There are several reasons why a firm does right issue, for example, to raise firm’s capital, investment expansion or to pay the debt. The objective of this study is to analyze the effect of the right issue on the abnormal return of the company. This research uses secondary data from the Indonesia Stock Exchange from 2014 to 2016. A sample of 18 firms met the criteria selection. The results show that there is no abnormal return in the days surrounding right issue announcement. The results also find that abnormal stock return in the days after right issue announcement is not lower or equal to the days before right issue announcement.